2020
DOI: 10.1177/0022022120949913
|View full text |Cite
|
Sign up to set email alerts
|

Bullies Get Away With It, But Not Everywhere: Mental Health Sequelae of Bullying in Chinese and German Students

Abstract: Bullying victimization is associated with adverse mental health consequences, while bullies suffer few or no adverse consequences in Western societies. Yet the universality of these consequences across western and eastern cultures is unknown. The current study investigated retrospective bullying experience in primary and secondary schools and its effects on adult mental health (depression, anxiety, stress, lifetime suicidal behavior, positive mental health, life satisfaction, social support, self-efficacy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
0
5
0
2
Order By: Relevance
“…Although there is a consistent body of literature on sibling bullying experiences in childhood or early adolescence and its psychopathological associations in early or late adolescence, it is frequently argued that the current literature is heavily based on the research that has been conducted in Western, Industrialised, Educated, Rich, and Democratic (WEIRD) countries (Lin et al, 2020;Wolke & Samara, 2004). While clear variations in the prevalence, type, and consequences of sibling bullying across cultures have been reported (Ji et al, 2016;Lin et al, 2020), still very little is known about sibling bullying in some non-WEIRD cultures, such as Turkey.…”
mentioning
confidence: 99%
“…Although there is a consistent body of literature on sibling bullying experiences in childhood or early adolescence and its psychopathological associations in early or late adolescence, it is frequently argued that the current literature is heavily based on the research that has been conducted in Western, Industrialised, Educated, Rich, and Democratic (WEIRD) countries (Lin et al, 2020;Wolke & Samara, 2004). While clear variations in the prevalence, type, and consequences of sibling bullying across cultures have been reported (Ji et al, 2016;Lin et al, 2020), still very little is known about sibling bullying in some non-WEIRD cultures, such as Turkey.…”
mentioning
confidence: 99%
“…Previous studies have found that traditional bullying perpetration/victimization ( 61 ) and cyberbullying perpetration/victimization ( 62 ) were related to the increase in adolescent depressive symptoms. A cross-cultural study shows that bullies (during adolescence) in China had more depressive symptoms in adulthood compared to victims, which emphasizes the impact of bullying ( 63 ). Adolescents who bully others were found to have more psychological and physical problems than their peers and had an increased risk for depression ( 64 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that higher perceived social support ( 23 , 24 ), especially parental support ( 25 ), was related to lower self-harm prevalence among adolescents. Moreover, a study of 5,012 Chinese university students reported that BV was associated with a lower level of perceived social support ( 26 ). Some researchers further explored the relationship between BV and different types of perceived social support and found that BV was inversely associated with parental support ( 27 ) and teenagers who were bullied received less support from parents and peers ( 28 ).…”
Section: Introductionmentioning
confidence: 99%